Urinary biomarkers in lupus nephritis - Aragón, Cristian C. (J Transl Autoimmun, 2020)
Systemic lupus erythematosus (SLE) is the prototypical autoimmune disease that can affect any organ of the body. Multiple mechanisms may contribute to the pathophysiology of systemic lupus, including failure to remove apoptotic bodies, hyperactivity of self-reactive B and T lymphocytes, abnormal exposure to autoantigens, and increased levels of B-cell stimulatory cytokines. The involvement of the kidney, called lupus nephritis (LN), during the course of the disease affects between 30% and 60% of adult SLE patients, and up to 70% of children. LN is an immune-mediated glomerulonephritis that is a common and serious finding in patients with SLE. Nowadays, renal biopsy is considered the gold standard for classifying LN, besides its degree of activity or chronicity. Nevertheless, renal biopsy lacks the ability to predict which patients will respond to immunosuppressive therapy and is a costly and risky procedure that is not practical in the monitoring of LN because serial repetitions would be necessary. Consequently, many serum and urinary biomarkers have been studied in SLE patients for the complementary study of LN, existing conventional biomarkers like proteinuria, protein/creatinine ratio in spot urine, 24 ​h urine proteinuria, creatinine clearance, among others and non-conventional biomarkers, like Monocyte chemoattractant protein-1 (MCP-1), have been correlated with the histological findings of the different types of LN. In this article, we review the advances in lupus nephritis urinary biomarkers. Such markers ideally should be capable of predicting early sub-clinical flares and could be used to follow response to therapy. In addition, some of these markers have been found to be involved in the pathogenesis of lupus nephritis.